The validity and reliability of an instrument to evaluate the practices of learning organization - Saraswathy Kullan; Mahaliza Mansor; Rosnah Ishak (Institute of Advanced Engineering and Science, 2022)
The future of students learning, and excellence of schools absolutely depend on the competence, skills, and expertise of its teachers. This study aimed to report on the validity and reliability of the practices of the learning organization instrument. The dimension of the learning organization questionnaire (DLOQ) instrument was used for the validity and reliability practices of learning organization among teachers. A total of 50 teachers who were selected at random from four indigenous primary schools located in Negeri Sembilan, Malaysia were the respondents in this survey study. The results showed: i) The item-content validity index (I-CVI) value achieved was between 0.67 to 1.00; ii) The scale-content validity index (S-CVI) value between 0.95 to 1.00; and iii) The modified kappa statistic between 0.57 to 1.00, proved that the DLOQ instrument adapted in this study had a high content validity. Hence, Cronbach’s Alpha values, Cronbach’s alpha if item deleted, inter-item correlation and corrected item-total correlation also explained that this instrument had high reliability. Therefore, the DLOQ instrument was reliable to measure characteristics of learning organization practices in the context of indigenous primary schools, Malaysia. In line with this, the practices of learning organization among teachers in schools especially primary schools need to be fully applied and implemented to produce more broadly skilled teachers, competent, have a high quality of teaching, able to produce students with high marketability, maintaining the sustainability of schools and educational institutions.